DARI KELAS KE KARIER: ANALISIS PSIKOLOGIS DAN SOSIOEKONOMI MINAT SISWA SMA MELANJUTKAN PENDIDIKAN TINGGI UNTUK SDM UNGGUL KALIMANTAN BARAT - Wahyuningsih, Devi; Ansyah, Feri (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the factors influencing high school students’ interest in pursuing higher education in West Kalimantan using a mixed-methods sequential explanatory approach. Quantitative data were collected from 200 respondents (100 in Pontianak, 100 in Kubu Raya) through a Likert-scale questionnaire and analyzed using SEM-PLS, while qualitative data were obtained from semi-structured interviews with students and school counselors/homeroom teachers, then analyzed thematically. The quantitative findings indicate that access to higher education information (O = 0.492; p < 0.001) and intrinsic–extrinsic motivation (O = 0.188; p = 0.032) significantly and positively affect students’ intention to continue to college. Conversely, parental support showed a significant negative effect (O = -0.188; p = 0.001), suggesting potential pressure. Socioeconomic status did not directly affect interest but influenced it indirectly through parental support with a negative direction. Although self-efficacy increased after training, it was not statistically significant in shaping students’ decision to pursue higher education. The qualitative analysis reinforced these results, highlighting financial barriers, limited access to information, and gender dynamics: female students were more encouraged to attend college, while male students tended to prioritize work.